(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Primary healthcare managers at the Upazila Health Complex (UHC) level play a vital role in ensuring the effective delivery of essential health services in Bangladesh. However, there is limited empirical evidence assessing their management capabilities. This study aimed to evaluate the management skills of primary healthcare managers in selected UHCs across Bangladesh, with a focus on identifying areas of strength and gaps requiring targeted improvement. Methods: The descriptive cross-sectional study was conducted over six months among 230 primary healthcare managers from 59 UHCs across four divisions of Bangladesh. Participants included Upazila Health and Family Planning Officers (UH&FPOs), Upazila Family Planning Officers (UFPOs), Resident Medical Officers (RMOs), and Nursing Supervisors. Data were collected using a pre-tested, structured questionnaire adapted from a validated scale developed by Kitreerawutiwong et al., which measured nine key dimensions of management skills: leadership, communication, partnership, system thinking, professionalism, emotional intelligence, proactive approach, financial planning, and information management. Multistage sampling was applied, and data were analyzed using SPSS version 25. Ethical approval was obtained from the Institutional Review Board (IRB) of NIPSOM. Informed consent was obtained from all participants. Results: Of the 230 respondents, 67% were male, and 61.3% had over one year of managerial experience. While 46.1% held MBBS degrees, only 3.9% had an MPH qualification, and 54.3% had received formal management training. Based on mean score classifications, 44.3% of managers demonstrated good management skills, 50.4% had average skills, and 5.2% exhibited poor skills. Strengths were observed in professionalism (mean score: 4.3), leadership (4.2), and communication (4.1). However, lower performance was noted in financial planning (3.8) and information management (3.6), indicating critical capacity gaps. Conclusions: This study highlights that while primary healthcare managers in Bangladesh possess foundational competencies in several management domains, deficiencies in financial planning and information management persist. Addressing these gaps through targeted, context-specific training programs is essential to strengthen managerial effectiveness and enhance the performance of UHCs. Policymakers should prioritize the integration of structured capacity-building initiatives within the national health workforce development strategy. JOPSOM 2024; 43(1): 59-66